Handheld Navigation Device and Patient-Specific Cutting Guides Result in Similar Coronal Alignment for Primary Total Knee Arthroplasty: A Retrospective Matched Cohort Study. Issue 3 (October 2016) - Steinhaus, Michael E.; McLawhorn, Alexander S.; Richardson, Shawn S.; Maher, Patrick; Mayman, David J.
Background: Proper alignment of total knee arthroplasty (TKA) is essential for TKA function and may reduce the risk of aseptic failure. Technologies that prevent malalignment may reduce the risk of revision surgery. Questions/Purposes: The purpose of this study was to compare two competing TKA systems that purport improved alignment: patient-specific instrumentation (PSI), and a handheld portable navigation device (NAV). Methods: After IRB approval, 49 consecutive PSI TKAs (40 patients) were matched based on preoperative characteristics to 49 NAV TKAs (40 patients) performed by a single surgeon. A blinded observer measured alignment on digital radiographs. Operating room records were reviewed for procedure times. Two-tailed paired sample t tests and McNemar's test were used as appropriate. Alpha level was 0.05 for all tests. Results: Preoperative cohort characteristics were not different. Mean postoperative long-leg mechanical alignment was within ±1° of neutral for both groups, although statistically different ( p = 0.026). There were no other significant differences in coronal alignment. PSI exhibited significantly greater posterior tibial slope (4.4°) compared to NAV (2.7°) ( p = 0.004); PSI resulted in significantly more outliers (>6°; p = 0.004). Procedure time for unilateral TKAs was lower for PSI (74.4 min) compared to that for NAV (80.6 min; p = 0.023). Conclusion: NAV and PSI technologies provided excellent coronal plane alignment. NAV was better for sagittal tibial slope, while PSI procedure times were shorter for unilateral TKA. The impact of these technologies on patient-reported outcomes and TKA survivorship is controversial and should be the focus of future research.